2010
DOI: 10.1111/j.1472-765x.2009.02758.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of ARAD microfibre filtration and LAMP methodology for simple, rapid and cost-effective detection of human pathogenic Giardia duodenalis and Cryptosporidium spp. in drinking water

Abstract: Aims:  In this study, we report a new, simple methodology for the monitoring of Cryptosporidium oocysts and Giardia cysts in drinking water samples, ranging from 10‐ to 1000‐l, which combines a new ARAD microfibre filtration of the (oo)cysts from drinking water and loop‐mediated isothermal amplification (LAMP) of a human pathogenic Cryptosporidium parvum, Cryptosporidium hominis, Cryptosporidium meleagridis and Giardia duodenalis Assemblage A and B specific DNA sequence. Methods and Results:  During the evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…The genomic DNA from the samples (water spiked with G. duodenalis cysts) was extracted and then EF-1α LAMP was performed. The results showed that LAMP reaction was not afected by inhibitors in any of the samples tested [42].…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…The genomic DNA from the samples (water spiked with G. duodenalis cysts) was extracted and then EF-1α LAMP was performed. The results showed that LAMP reaction was not afected by inhibitors in any of the samples tested [42].…”
mentioning
confidence: 63%
“…Next, 8 U Bst DNA polymerase large fragments were added followed by incubation at 63°C for 120 min and heating at 80°C for 7 min to terminate the reaction [40]. In a consecutive report, the primer concentration was as follows: 40 pmol each of FIP and BIP primers, 20 pmol each of LF and LB primers, and 5 pmol each of F3 and B3 primers [41,42].…”
Section: Current Topics In Giardiasis 118mentioning
confidence: 99%
“…Çalışmamıza dahil edilen 39 izolata, EF-1α gen bölgesi için LAMP ve bg gen bölgesi için PCR yöntemi uygulanmış ve bu testlerin pozitifl ik oranları sırasıyla %82 ve %48.7 olarak saptanmıştır. Çalışmamızda, diğer çalışmalara [18][19][20] benzer olarak, LAMP testinde daha yüksek pozitifl ik elde edilmiştir.…”
Section: Discussionunclassified
“…(BAKHEIT et al, 2008;KARANIS, 2009;PLUTZER et al, 2010b;MAHMOUDI et al, 2013). A study by Mahmoudi et al (2013) with water samples from Iranian rivers, demonstrated that LAMP is a good tool to complement PCR, because it is not affected by the presence of inhibitors, thereby identifying positive samples that tested negative by conventional PCR.…”
Section: Molecular Identification For Characterization Of Infection Smentioning
confidence: 99%
“…The importance of this form of contamination varies according to the characteristics of the hydrographic basin and depends on the type of exploration activities located in the catchment area (JIANG et al, 2005). Contamination of wells and springs by the dispersion of these protozoa and contamination of public or domestic reservoirs represent danger to the population, as there are no barriers between the reservoirs and the consumer, and generally, a reservoir serves a large portion of the population (GAUT et al, 2008;PULESTON et al, 2014).…”
Section: Cryptosporidium and Giardia: Waterborne Organisms And Their mentioning
confidence: 99%